Strategi Pelayanan Pastoral bagi Remaja di Era Digital - Kristian, Samuel (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2023)
Teenage years is the moment of humans in which they experience many changes in life, both physically and emotionally. A lot of things they believed as children will change in teenage years. It is also seen as a critical and defining period in life since what they experience during this time will have a great impact in their future. In the time of digital era, teenagers need to be equipped with a strong and true foundation of faith so that they can live according to the God's Words. However, the challenges are that the pastoral care for teenagers cannot be done using outdated methods. The characteristics of teenagers in digital era who wants everything to be fast, convenient, and accessible from anywhere, and the tendency of being attached to gadget must be taken into consideration in developing its strategy so that the Words of God can be effectively received by them. This paper aims to explore the unique characteristics of teenagers in the digital era, challenges which arise, and the most effective and efficient pastoral care strategies. The research is done using literature study method. The data is collected from various books, articles and journals. It is found that technology is now a part of everyone’s life, especially teenagers. Thus, pastoral care should integrate the use of technology. The method of the sermon should be changed, from one-way sermon to discussions, question-answer sessions, etc. The theme of the sermon should also be designed to the things that meet teenagers’ life.